Vice Chancellors and University Education Sustainability in Nigeria: Challenges and Way Forward - Ogunode, Niyi Jacob; Ayeni, Evans Oluwagbamila (Journal of Higher Education and Academic Advancement, 2024)
The study examined Vice Chancellors and University Education Sustainability in Nigeria: Challenges and Way Forward. Vice Chancellors are major players and chief executive officers in the universities' administrations; hence their roles cannot be underestimated. The social and economic development of the universities depends on the job performance of the Vice-Chancellors. This paper critically looked at the concept of Vice-chancellors and the roles and functions of Vice-chancellors in the university system. The paper also examined factors that enhance the job performance of Vice-chancellors in the university system in Nigeria. This study attempts to provide an answer to the research question that says; how has the Vice Chancellors impacted University Education for Sustainability in Nigeria? The study employed an ex-post facto research method, using secondary data that were collected from print and online publications. Content analysis was the method of analysis. The paper established that the independence of Vice Chancellors, training and retraining, adequate funding, effective supervision and provisions of adequate working resources are the factors that will enhance Vice Chancellors' job performance and enable university education to be able to perform their roles in Nigerian society. Based on the findings of this study, the following recommendations were made: The Federal Government of Nigeria and the state governments should provide adequate funds for university administrators, infrastructure facilities, adequate working resources, grant autonomy to universities and ensure effective training and retraining programmes and supervision. The suggested solution will enable the university administrators (Vice Chancellors among others) to be effective in the discharge of their roles in the universities and make university education perform its role of social and economic development.